1997
DOI: 10.1016/s0022-5223(97)70405-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct vasodilator effect of milrinone, an inotropic drug, on arterial coronary bypass grafts

Abstract: Milrinone is an inotropic drug with vasodilator activity that has been shown to be useful in increasing cardiac output and decreasing wedge pressure. Despite these advantages, it is unknown whether this drug can be used for the treatment of perioperative spasm of coronary bypass grafts. This study was undertaken to investigate the in vitro vascular effect of milrinone on internal thoracic arteries obtained from patients undergoing coronary artery bypass grafting. The results showed that milrinone produced a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The Phosphodiesterase III inhibitor (PDE III-I) is currently considered to be very effective to prevent vasospasm. The systemic administration of PDE III-I has been reported to increase graft blood flow [9,[23][24][25]. A study on the direct injection into a graft is rare.…”
Section: Introductionmentioning
confidence: 99%
“…The Phosphodiesterase III inhibitor (PDE III-I) is currently considered to be very effective to prevent vasospasm. The systemic administration of PDE III-I has been reported to increase graft blood flow [9,[23][24][25]. A study on the direct injection into a graft is rare.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant decrease in CO may occur despite relatively well-preserved mean SAP and it is conceivable that the cumulative effect of these transient episodes of reduced CO and reduced perfusion pressure due to elevated RAP in the course of distal anastomoses during OPCAB resulted in a degree of ischemic organ injury at least comparable to CPB [18]. Since milrinone has been reported to have little effect on myocardial oxygen consumption [10] unlike other inotropic agents [11] and to dilate arterial bypass graft [12,13], maintaining or increasing CI and SVI within acceptable range with milrinone in patients with low pre-graft CI was considered to be useful. However, the effect of milrinone on post-operative course seemed to be subclinical.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant increase in myocardial oxygen consumption [10] and its myocardial oxygen consumption is lower compared to that of dobutamine [11]. Milrinone has a direct vasodilating effect on arterial grafts [12] and also increases the blood flow in grafted internal mammary artery after cardiopulmonary bypass [13]. It's positive effect on myocardial contractility and coronary blood flow with minimal increase in heart rate and myocardial oxygen consumption make milrinone an inotropic agent of choice for patients undergoing OPCAB.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports by Salmenpera and Levy 8 and Liu et al 15 suggested that phosphodiesterase inhibitors may be useful for preventing or treating an IMA spasm, using human IMA rings. Since toborinone possesses a phosphodiesterase inhibitory action, we performed this experiment in an explanted canine IMA model.…”
Section: Discussionmentioning
confidence: 99%